Integrating Protocol Schedules with Patients’ Personal Calendars - Civan, Andrea (American Medical Informatics Association, 2006)
We propose a new approach for integrating protocol care schedules into patients’ personal calendars. This approach could provide patients with greater control over their current and future scheduling demands as they seek and receive protocol-based care.